Review of Progress Rural Industries Projects Programme 1965-66 - Planning Commission (Planning Commission, 1967)
The previous Review of Progress of the Rural Industries Projects Programme for the year 1964-65 was issued in August, 1965. It was hoped to bring out the review of the progress for the year 1965-66 by the end of 1966. However due to unavoidable reasons, including the delay in obtaining data from the project authorities, verification of some figures, etc., the finalisation of the present Review of Progress 1965-66 has taken somewhat longer than expected.
Planning Commission Rural Industries Planning Committee